Ответ:
1. ( b + x )^2 = b^2 + 2bx + x^2 (ответ Б).
2. 9 - а^2 = ( 3 - a )( 3 + a ) (ответ Б).
3. ( 2b + 5 )( 2b - 5) = 4b^2 - 25 (ответ Г).
4. y^2 - 2yx + x^2 = ( y - x )^2 (ответ А).
5. 1 — В;
2 — А;
3 — Б;
4 — Г.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1. ( b + x )^2 = b^2 + 2bx + x^2 (ответ Б).
2. 9 - а^2 = ( 3 - a )( 3 + a ) (ответ Б).
3. ( 2b + 5 )( 2b - 5) = 4b^2 - 25 (ответ Г).
4. y^2 - 2yx + x^2 = ( y - x )^2 (ответ А).
5. 1 — В;
2 — А;
3 — Б;
4 — Г.